Complete mitochondrial genome of Pnyxia scabiei (Diptera: Sciaridae) - Caixia Liu; Qingyun Wang; Hong Wu; Junhao Huang (Mitochondrial DNA. Part B. Resources, 2021)
The potato scab-gnat, Pnyxia scabiei, was recorded as a pest attacking potato tubers and greenhouse cucumber plants. The mitochondrial genome of a total length of 15,437 bp was sequenced, including 13 protein-coding genes, 22 tRNA genes, and two rRNA genes with A + T content of 77.2%. Six gene overlaps were found from 1 to 34 bp. Phylogenetic analysis showed that P. scabiei was closely related to Trichosia lengersdorfi + Sciara ruficauda. The study provided further data for species diversification in Sciaridae.